ANALISIS RESPON BANGUNAN GEDUNG LIMA LANTAI MENGGUNAKAN BASE ISOLATOR DI KOTA PADANG - Ade Faisal; Azmi Arief (Portal: Jurnal Teknik Sipil, 2017)
Earthquakes are a natural phenomenon that can’t be circumvented by humans where the incident resulted in material losses and casualties. The impact was mostly occur by the damage and the collapse of a building. The technology developed in recent foundation is very influential to minimize the collapse of a structure due to the earthquake. Base Isolator is a breakthrough cutting edge technology that is placed on the foundation that serves to reduce the effects of earthquakes. Stiffness in the structure also affected the durability of building damage and collapse. The brick wall serves to increase the stiffness of a building structure. This final project aims to determine and compare the response of structures using technology base isolator and fixed base. The parameters are reviewed, namely natural period (T), the shear force (V), and deviation (δ). Analysis used is equivalent static analysis and response spectrum analysis. There are four models that became a point of comparison, the fixed base structure without a brick wall, fixed base with brick walls, base isolator without a brick wall, and base isolator with brick walls.Keywords: Earthquakes, Base Isolator, Stiffness, Technology Foundation, Brick Walls